Penurunan Skor Agression Self-Control Pasien Resiko Perilaku Kekerasan dengan Terapi Musik - Widyo Subagyo; Dyah Wahyuningsih; Mukhadiono Mukhadiono (JURNAL KEPERAWATAN MERSI, 2018)
Background: Violence is a condition in which a person   does a dangerous action threatening physically  to him/herself or other(s). It usually goes with a rampage and uncontrolled restlessness. Due to the emotion and inappropriate coping, the behavior becomes aggressive and can hurt others. New Age is  a music genre which can transfer a mental experiences of positives, relax, inspiring, and comfortable. It has cultural elements, using binaural beats. The sound wave in it has potential to reduce the aggression self-control score. Objective: To find out the effect of music therapy to the reduction of Aggression Self-Control Score among the violence potential patients treated in the Sadewa ward of Banyumas hospital. Research Method:  It applied quasi experiment with a design of non randomized control group with pretest and posttest design. The population was 58 patients taken as a sample, using purposive sampling. It then gave 19 patients of experiment group and another group of 19 patients as the control group. The statistic analysis used was paired t-test and independent t-test. Finding: The result of paired t-test among the experiment group after they were treated by the music therapy indicates that the aggression self-control score significantly decreases with the t value of -13,84, and p=0,00. Meanwhile the result of independent t-test between the experiment and control groups shows a very significant difference of aggression self-control score with t value of 27,16 and p=0,00. Conclusion: The music therapy of Yanni’s New Age reduces the aggression self-control score among the patients with violence potential.